2019
DOI: 10.1007/s00426-019-01151-z
|View full text |Cite
|
Sign up to set email alerts
|

Grasping and perception are both affected by irrelevant information and secondary tasks: new evidence from the Garner paradigm

Abstract: In their Perception-Action Model (PAM), Goodale and Milner (1992) proposed functionally independent and encapsulated processing of visual information for action and perception. In this context, they postulated that visual input for action is processed in an automatized and analytic manner, which renders visuomotor behaviour immune to perceptual interferences or multitasking costs due to sharing of cognitive resources. Here, we investigate the well-known Garner Interference effect under dual-and single-task con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In normally sighted individuals, grasping resists a number of effects that influence perceptual judgments: grasp aperture resists the target size-distorting influence of illusory backgrounds (e.g, Whitwell et al, 2016Whitwell et al, , 2018Carther-Krone et al, 2020;Navon and Ganel, 2020;Smeets et al, 2020; but see Kopiske et al, 2016); it resists Weber's Law, failing to show a positive relationship between precision and stimulus size (e.g., Ganel et al, 2008;Holmes et al, 2011;Heath et al, 2012;Ozana and Ganel, 2018b; but see Foster and Franz, 2013); and grasp preparation time is not prolonged in the filtering condition of the Garner interference paradigm, in which choice-response times increase when both the relevant and irrelevant dimensions of the target are varied (e.g., Goodale, 2003, 2014;Eloka et al, 2015;Freud and Ganel, 2015;Ozana and Ganel, 2018a; but see Löhr-Limpens et al, 2020).…”
Section: The Visual Control Of Natural Reaching and Grasping Is Largementioning
confidence: 99%
“…In normally sighted individuals, grasping resists a number of effects that influence perceptual judgments: grasp aperture resists the target size-distorting influence of illusory backgrounds (e.g, Whitwell et al, 2016Whitwell et al, , 2018Carther-Krone et al, 2020;Navon and Ganel, 2020;Smeets et al, 2020; but see Kopiske et al, 2016); it resists Weber's Law, failing to show a positive relationship between precision and stimulus size (e.g., Ganel et al, 2008;Holmes et al, 2011;Heath et al, 2012;Ozana and Ganel, 2018b; but see Foster and Franz, 2013); and grasp preparation time is not prolonged in the filtering condition of the Garner interference paradigm, in which choice-response times increase when both the relevant and irrelevant dimensions of the target are varied (e.g., Goodale, 2003, 2014;Eloka et al, 2015;Freud and Ganel, 2015;Ozana and Ganel, 2018a; but see Löhr-Limpens et al, 2020).…”
Section: The Visual Control Of Natural Reaching and Grasping Is Largementioning
confidence: 99%
“…Finally, Singhal et al [20] showed that a more general cognitive phenomenon, namely the finding that the concurrent execution of two tasks creates performance costs for at least one of the two tasks, reliably occurs in tasks that can be assigned to the perceptual system but is much less prominent in tasks assigned to the visuomotor system. However, all these approaches have been met with counter-evidence and are currently bogged down in controversy [21,22,23,24,25,26,27,28,29].…”
Section: Introductionmentioning
confidence: 99%